Taxonomic and bionomic notes on the white spot assassin bug Platymeris biguttatus (Linnaeus) (Hemiptera: Reduviidae: Reduviinae) - Li, Hu; Zhao, Guangyu; Cao, Liangming; Xu, Kang; Cai, Wanzhi (Zootaxa, 2010)
The white spot assassin bug Platymeris biguttatus, a large African species is redescribed, along with male genitalia. Some biological notes on life history, nymphal instars, predatory behavior, oviposition, emergence and colonization, etc. based on laboratory rearing and observations are provided.